EFEKTIVITAS AKUPUNKTUR CHUZHEN UNTUK TERAPI SINDROM SERVIKAL : LAPORAN KASUS - Willie Japaries; Yelini Fan Hardi; Zhang Hui (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
Chuzhen acupuncture or in English-language publications called “pestle needle” or “Chuzhen acupuncture” is a non-invasive method of acupuncture therapy by massaging along the meridians and pressing on acupuncture points. So Chuzhen therapy is a combination of massage (“tuina”) and acupressure. Chuzhen's therapeutic meridian is called “Hechelu”, located along and parallel to the Du or GV (governing vessel) meridian and the Ren or CV (conception vessel) meridian. The hechelu in the back of the neck used for the treatment of cervical syndrome consists of seven lines, namely one running on the median line according to the GV meridian along the spine, three lines each on the left and on the right running parallel to the GV, spaced about 0.5 inches, 1 and 1.5 inches lateral to the GV, from the level of Naohu point (GV17) at the upper border of the atlas vertebra, to the level of Dazhui point (GV14) at the base of the seventh cervical vertebra (7 cervical vertebra).